Using Microdosing to Induct Patients Into a Long-Acting Injectable Buprenorphine Depot Medication in Low Threshold Community Settings: A Case Study - Tay Wee Teck, Joseph; Baldacchino, Alexander; Gibson, Lauren; Lafferty, Con (Frontiers in Pharmacology, 2021)
Healthcare innovation has never been more important as it is now when the world is facing up to the unprecedented challenges brought by the COVID-19 pandemic. Within addictions services in Scotland, the priority has been to tackle our rising drug related death rate by maintaining and improving access to treatment while protecting frontline workers and managing operational challenges as a result of the pandemic. We present here a case study of five patients with opioid use disorder whose treatment represents a confluence of three important Medication Assisted Treatment (MAT) service innovations. The first was a low threshold drop in and outreach MAT service to rapidly and safely initiate opiate replacement therapy (ORT). The second was the provision of a microdosing regimen to enable same day induction to oral buprenorphine while minimizing the risk of precipitated opioid withdrawals and/or treatment disengagement. The third was rapid transitioning to an injectable long-acting buprenorphine depot which reduced unnecessary face to face patient contact and treatment non-adherence. This case study of five patients highlights the valuable role that buprenorphine microdosing can play in making induction to long-acting buprenorphine depot feasible to a broader range of patients, including those on a high dose methadone treatment regime.